2009
DOI: 10.1162/jocn.2009.21087
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Ventrolateral fMRI Response during Observation of Emotional Gestures Related to the Degree of Dopaminergic Impairment in Parkinson Disease

Abstract: Abstract& Recent findings point to a perceptive impairment of emotional facial expressions in patients diagnosed with Parkinson disease (PD). In these patients, administration of dopamine can modulate emotional facial recognition. We used fMRI to investigate differences in the functional activation in response to emotional and nonemotional gestures between PD patients and age-matched healthy controls (HC). In addition, we used PET to evaluate the striatal dopamine transporter availability (DAT) with [11 C]D-th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
46
1
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 67 publications
5
46
1
4
Order By: Relevance
“…Although activity in this region is sometimes observed during processing of affective social signals (Sprengelmeyer et al, 1998;Wildgruber et al, 2004;Ethofer et al, 2009;Lotze et al, 2009) this region appears to be primarily involved in value representation and stimulus evaluation (Kringelbach and Rolls, 2004). In line with this interpretation we found a positive correlation between lateral orbitofrontal activity and the participants' joy ratings, but not with their ability to decode facial emotional expressions.…”
Section: The Lateral Orbitofrontal Cortexsupporting
confidence: 78%
See 1 more Smart Citation
“…Although activity in this region is sometimes observed during processing of affective social signals (Sprengelmeyer et al, 1998;Wildgruber et al, 2004;Ethofer et al, 2009;Lotze et al, 2009) this region appears to be primarily involved in value representation and stimulus evaluation (Kringelbach and Rolls, 2004). In line with this interpretation we found a positive correlation between lateral orbitofrontal activity and the participants' joy ratings, but not with their ability to decode facial emotional expressions.…”
Section: The Lateral Orbitofrontal Cortexsupporting
confidence: 78%
“…Only the first of these studies (Le Jeune et al, 2008) found a positive relation between lateral orbitofrontal activity (glucose metabolism measured with PET) and facial emotion recognition in patients with Parkinson's disease. The other two studies assessed recognition of emotional gestures, but did not find a significant correlation between BOLD activity during observation of emotional gestures and emotional gesture recognition ability (Lotze et al, 2009) or grey matter volume and facial emotion recognition ability (Ibarretxe-Bilbao et al, 2009;note, however, that these authors report a positive correlation between grey matter loss in more distributed regions of the orbitofrontal cortex and emotion recognition impairment). Thus, orbitofrontal grey matter and neural activity seem to be altered in Parkinson's disease but these changes might not have a direct impact on social emotion recognition ability in these patients.…”
Section: The Lateral Orbitofrontal Cortexmentioning
confidence: 84%
“…Indeed, not only putaminal but also orbitofrontal and amygdalar presynaptic dopaminergic functions were altered in early PD 111. In addition, brain responses recordings during FER tasks have revealed decreases in striatal, amygdalar, and orbitofrontal activity and lower activation in analytic temporal facial recognition areas (STS and fusiform gyrus) 57, 72, 101, 112. Lotze et al112 have shown that the less dopamine transporter availability (DAT) present in the putamen, the lower the ventrolateral prefrontal cortex activation in response to emotional gestures and highlighted a positive correlation between the putaminal DAT reduction and the number of errors in emotional gestures recognition.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, brain responses recordings during FER tasks have revealed decreases in striatal, amygdalar, and orbitofrontal activity and lower activation in analytic temporal facial recognition areas (STS and fusiform gyrus) 57, 72, 101, 112. Lotze et al112 have shown that the less dopamine transporter availability (DAT) present in the putamen, the lower the ventrolateral prefrontal cortex activation in response to emotional gestures and highlighted a positive correlation between the putaminal DAT reduction and the number of errors in emotional gestures recognition. Similarly, morphometry analyses reported decreased gray‐matter volume in numerous limbic, paralimbic, and neocortical associative temporo‐occipital areas64, 66, 113, 114 and showed that the atrophy could be associated with the deficit, as gray‐matter volume in these regions correlated with patients' FER performance 64, 66.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation